(untitled) (AACINI - International Journal of Industrial Engineering, 2022)
The aim of this work was the development of a reference framework and methodology for the technical feasibility study of the use of collaborative robots in manufacturing SMEs. According to our previous study, the technical factor is one of the five evaluation variables for decision-making for the incorporation of Cobots in workstations, being them: the technical factor, the ergonometric factor, the quality, the economic-financial factor. and the regulatory one. This work has been carried out in three phases: (1) a systematic analysis of the literature regarding the use of Cobots in SMEs and its corresponding technical evaluation was carried out, (2) the evaluation method was selected, and (3) the applied to a case of incorporation of a Cobots in a workstation of a small company that manufactures electrical products in Argentina. This methodology collaborated with the decision-making of senior management to understand whether the activities of feeding, handling and assembling electrical parts and components could be carried out efficiently and effectively by means of a robotic arm.